2022
DOI: 10.1007/s12144-022-02759-y
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Daily Activities and Well-being during the COVID-19 Lockdown: Associations with Child and Family Characteristics

Abstract: Learning, leisure, social, and movement activities are essential facets of children´s development affecting their physical, mental, and social well-being. During the first Covid-19 lockdown and post-lockdown period, children´s everyday lives were disrupted and altered in significant ways for an extended period, raising several concerns regarding its negative effects. This study investigated children´s daily activities during the lockdown and post-lockdown period, considering child and family factors that influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Mothers were even the sole participants in seven included studies ( 43 , 44 , 47 , 52 , 53 , 57 , 65 ). Compared with mothers, the fathers' participation in research studies was low, so fathers were one of the respondents in ten included studies only [e.g., ( 32 , 39 , 45 , 46 , 48 , 49 , 51 , 60 62 , 64 )]. Studies using both parent-child dyads as informants were also dearth ( 40 , 45 , 56 , 58 , 60 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mothers were even the sole participants in seven included studies ( 43 , 44 , 47 , 52 , 53 , 57 , 65 ). Compared with mothers, the fathers' participation in research studies was low, so fathers were one of the respondents in ten included studies only [e.g., ( 32 , 39 , 45 , 46 , 48 , 49 , 51 , 60 62 , 64 )]. Studies using both parent-child dyads as informants were also dearth ( 40 , 45 , 56 , 58 , 60 ).…”
Section: Resultsmentioning
confidence: 99%
“…The temporary closure of schools and home confinement to mitigate the spread of COVID-19 translated to a sedentary lifestyle for children, including increased use of screen time and online interactions whereas face-to-face interaction time decreased significantly ( 68 ). Based on the cross-sectional data from Portuguese children studying in 3rd and 4th grade and their parents, Oliveira et al ( 60 ) found that there was a higher prevalence of sedentary behaviors including TV and gaming/internet, i.e., activities that required a higher amount of screen time, particularly among socioeconomically vulnerable children. There were gender differences in screen time, with girls spending more time on watching TV and socializing online.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study of 2-4-year-olds estimated that every additional hour per day that children watched TV or digital media is associated with a higher mean SDQ score for conduct problems 60 . Another study in primary school children found that playing and learning activities were linked to lower behavioral problems, active leisure was positively associated with physical well-being, and socialization and family activities were linked to better social well-being 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Conflicts arising out of the rapid increase in outdoor leisure sports participants in limited spaces have been primarily related to etiquette, space management, and space planning (22,23). For example, not wearing a mask correctly, talking too much, or drinking beverages during exercise increase others' anxiety about exposure to the virus and cause conflicts among participants (24,25).…”
Section: Introductionmentioning
confidence: 99%